Identification and Distribution of Palygorskite in a Petrocalcic Paleargid - Baig, Muhammad Anwar; Tice, Kathy R. (Journal of Himalayan Earth Sciences, 1997)
Palygorskite is a chain lattice phyllosilicate typically found in arid zone soils containing a calcic or petrocalcic horizon. Its presence was verified in a Petrocalcic Paleargid in the central desert of Baja California using several diagnostic techniques. X-ray diffraction of the clay and medium silt fractions of each horizon showed characteristic palygorskite peaks at approximately 10.4, 6.4, 3.6 and 3.2oA. Heating processes decreased the intensity of the 10.4oA peak and resulted in new peaks at 9.3 and 4.7oA in the Ckq horizon. Peaks in the clay fraction became broader and less intense, indicating lower concentration and poor crystallinity of palygorskite with decreasing depth. Thermal and infrared spectroscopic analyses corroborated XRD data. TGA weight losses occurred at 50-150, 175-225 and 375-535oC, corresponding to loss of hygroscopic water, loss of zeolitic water and dehydroxylation, respectively. Decomposition weight loss was not seen at the characteristic high temperature (690-770oC). Additionally, IR absorbance bands were characteristic of palygorskite, occurring at 3620, 3580, 3530, 3415, 3290, 1660, 1180, 1030, 1000 and 930 cm-1. Finally, the TEM analysis revealed presence of acicular particles, increasing in abundance with depth, which were morphologically identical to palygorskite. Thus, the palygorskite was identified in the clay and medium silt fractions of the soil, showing its concentration and the degree of crystallinity with increased depth.